Aluation of microbiological contamination of endodontic files in primary packaging – new (Research, Society and Development, 2022)
Endodontic files are essential elements in the performance of Endodontics. Success depends on assertive diagnosis, adequate planning and correct execution of the technique. All this associated with the care with the safety of the aseptic chain. The present study aims to evaluate the existence of microbiological contamination in new endodontic files and their respective packaging. Sometimes, professionals use new files, recently removed from the packaging without sterilization, because they believe that cross-contamination occurs from one patient to another, and the file being new, this contamination is not present. It was then proposed the microbiological control from the collection of the surfaces of the new files and their respective packages. After collection, each group was seeded in Petri dishes. The culture media selected were Blood Agar, Mannitol Agar and Mac Conkey Agar. Then, the plates were incubated in a conventional oven at 37°C for 48 hours. The contamination reading was performed and the results were measured via gram staining. There was microbiological growth of 100% of the endodontic files in the Blood Agar culture medium - which showed growth of gram-positive cocci microorganisms. There was microbiological growth on the packaging of the files on blood agar with growth of gram-positive cocci, Mannitol Agar - with growth of gram-negative cocci and Mac Conkey Agar with gram-negative cocci and gram-positive bacilli. Thus, it is concluded that there is microbiological contamination in endodontic files in primarys/new packaging and there is a need for sterilization prior to use.